CULTURALLY-SPECIFIC RISK AND RESILIENCE FACTORS THAT MODERATE THE RELATIONSHIP BETWEEN REPRODUCTIVE COERCION AND ADVERSE HEALTH OUTCOMES AMONG LATINX INDIVIDUALS - (:unkn) unknown (My University, 2024)
Reproductive coercion (e.g., one partner controlling the reproductive decision making of the other) is a serious public health problem that is associated with a number of adverse health outcomes. Reproductive coercion has been shown to disproportionately affect Latinx people who can become pregnant; however, little is known about the cultural factors, such as familism, ethnic identity pride, social support, and acculturative stress, that may mitigate or exacerbate the risk of experiencing adverse health outcomes associated with reproductive coercion. Thus, using a non-clinical sample (N=160) of Latinx-identifying adults, the current cross-sectional study examined (1) the associations between reproductive coercion and adverse health outcomes and (2) culturally-specific risk and resilience factors that may moderate the relationship between reproductive coercion and adverse health outcomes among Latinx individuals. Lifetime prevalence of experiencing any form of reproductive coercion was 46.3% in this sample. Results indicated that reproductive coercion was associated with poor mental and behavioral health outcomes, including alcohol use, depression, anxiety, and stress, and PTSD symptoms. Further, reproductive coercion was also shown to be associated with high utilization of reproductive health services (e.g., pregnancy testing, STI screening, emergency contraception). Contrary to our hypotheses, the relationships between reproductive coercion and adverse health outcomes were not moderated by culturally-specific risk and resilience factors. These findings suggest a need for universal screening for reproductive coercion and other forms as IPV, as well as public health policy that ensures access to high quality reproductive health care. Future research is needed to replicate and extend these findings and identify other culturally-relevant factors that may impact health outcomes related to reproductive coercion.